2010
DOI: 10.1128/aac.00679-09
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Artemether-Lumefantrine and Artesunate-Amodiaquine in Children in Kampala, Uganda

Abstract: The World Health Organization recommends the use of artemisinin-based combination therapies (ACTs) for the treatment of uncomplicated malaria. The two most widely adopted ACT regimens are artemether (AR)-lumefantrine (LR) (the combination is abbreviated AL) and amodiaquine (AQ)-artesunate (AS). Pharmacokinetic (PK) data informing the optimum dosing of these drug regimens is limited, especially in children. We evaluated PK parameters in Ugandan children aged 5 to 13 years with uncomplicated malaria treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
63
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 37 publications
7
63
2
Order By: Relevance
“…In one study conducted in Ugandan children (26.5-kg body weight, on average), the geometric mean lumefantrine C max was 6.8 g/ml and the AUC from times zero to 120 h after the last dose amounted to 195 g ⅐ h/ml (19). The lower AUC compared to our analysis can be explained by different sample collection protocols.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…In one study conducted in Ugandan children (26.5-kg body weight, on average), the geometric mean lumefantrine C max was 6.8 g/ml and the AUC from times zero to 120 h after the last dose amounted to 195 g ⅐ h/ml (19). The lower AUC compared to our analysis can be explained by different sample collection protocols.…”
Section: Discussioncontrasting
confidence: 39%
“…These were 186 Ϯ 125 ng/ml for artemether and 101 Ϯ 58 ng/ml for DHA after the first dose of A-L (14). A recently published small study of children from Uganda assessed the pharmacokinetics of artemether and DHA after the third dose of an A-L tablet (19). The different study design limits the comparability of those pharmacokinetic results with the results of our analysis.…”
Section: Discussionmentioning
confidence: 39%
“…This is supported by comparative pharmacokinetic studies in children and adults that found that children had a higher clearance (28) or a lower PQ exposure at critical times during the illness (44). These concerns have also been raised for other antimalarial drugs (8,33) and reflect pharmacokinetic effects due to the effects of body size, maturation, and organ function (3). Although only children aged between 5 and 10 years were included in the present study, we found that recurrence of parasitemia was associated with a lower PQ AUC resulting from a lower milligram/kilogram dose, consistent with other studies of DHA-PQ tetraphosphate (16).…”
Section: Discussionsupporting
confidence: 51%
“…Although the tolerability, safety, efficacy, and pharmacokinetics (PK) properties of DHA-PQ tetraphosphate have been widely investigated in children and adults (27,28,36,44,49), there are limited data relating to the efficacy and tolerability of 46) and no studies of the pharmacokinetics of this novel combination in malaria-infected patients. Concerns have been raised regarding possible underdosing in children for a number of antimalarial drugs (8,33), including PQ (27,36,49). Although children have been included in studies of PQ pharmacokinetics (28, 44), only one pharmacokinetic study of ART has specifically enrolled pediatric patients (40).…”
mentioning
confidence: 99%
“…The conversion of AM to DHA is catalyzed by cytochrome P450 (P450) (van Agtmael et al, 1999b,c;Navaratnam et al, 2000). However, the elimination half-life of AM is very short, and it shows large interindividual variability in pharmacokinetic parameters (Na Bangchang et al, 1994;Mordi et al, 1997;van Agtmael et al, 1999a;Lefèvre et al, 2002;Ali et al, 2010;Mwesigwa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%